Business restructuring law in Europe: making a fresh start. Issue 1 (2nd January 2017) - McCormack, Gerard
ABSTRACT: This paper critically examines a new European approach to business failure and insolvency. It addresses the broader political dimensions of the subject and sets the new European approach in the context of the objectives of insolvency law to rescue viable businesses and to liquidate non-viable ones. The comparable US procedure – Chapter 11 of the Bankruptcy Code – is used as a reference point for detailed analysis. The paper suggests that the new approach is of particular importance and adds value in those EU Member States that have underdeveloped restructuring frameworks. It is also suggested however, that any measures of legislative harmonisation should be of the minimum harmonisation variety leaving scope for regulatory differentiation and allowing national governments to build on local restructuring frameworks and domestic business practices that work well.